13 - (6,6 - 2 8/15) * 3 50 - (3 3/4 + 6,5) : 0,25

+3
Ответы (1)
  1. 22 июня, 08:52
    0
    1) Вычислим выражение 13 - (6,6 - 2 8/15) * 3 по действиям:

    6,6 - 2 8/15 = 6,6 - 38/15 = 6 6/10 - 38/15 = 6 3/5 - 38/15 = 33/5 - 38/15 = 33 * 3/15 - 38/15 = 99/15 - 38/15 = 61/15, тогда 13 - 61/15 * 3;

    2) 61/15 * 3 = 61/5 = 12,2, тогда 13 - 12,2;

    3) 13 - 12,2 = 1 - 0,2 = 0,8.

    Ответ: 0,8.

    2) 50 - (3 3/4 + 6,5) / 0,25 = 50 - (3,75 + 6,5) / 0,25 = 50 - 10,25/0,25 = 50 - 1 025/25 = 50 - 41 = 10 - 1 = 9.

    Ответ: 9.
Знаешь ответ на этот вопрос?